A study on the impact of emotional intelligence and resiliency on stress management among academic staff in Malaysian private universities - Wong, Jasper Wei Sheng; Kong, Kah Wai; Hew, Winnie Song Lin; Yong, Siew Ling (2023)
Academic staff members in private universities are faced with numerous work-related stressors that can negatively impact their mental health and job performance. In addition to the traditional stressors such as excessive workload and limited support, the COVID-19 pandemic has added a new layer of stress for academic staff, including rapid transitions to online teaching, increased workloads, and concerns about job security. Hence, this study aims to investigate the impact of emotional intelligence and resiliency on stress management among academic staff in Malaysian private universities. Specifically, the study sought to achieve the followings: (1) To study the impact between emotional intelligence and stress management among academic staff in Malaysian Private Universities; (2) To study the impact between resiliency and stress management among academic staff in Malaysian Private Universities. The research is based on a quantitative approach using questionnaire as the primary data collection tool. The collected data is analyzed using Statistical Package for Social Science (SPSS).